COLLEGE STUDENTS’ PERCEPTION TOWARD ENGLISH LEARNING THROUGH GENSHIN IMPACT - Eti Dwi Andriani; Maya Rahmawati (IKIP Siliwangi, 2022)
This study aims to explore students' perceptions of language learning through online games. The approach used in this research is a qualitative approach to complement this research. The participants involved in this study were fourth-year college students of English language education at a university in Karawang. A structured interview was used as an instrument used in this study to answer the researcher's questions. The results shows that participants have a good and positive perception. This shows that they feel motivated, interested, enthusiastic, and fond of learning English through Genshin Impact because it is fun and it doesn't feel like learning. Besides, it is also easy to access and more interesting than learning to listen formally. There are several reasons why they can develop their English through Genshin Impact, namely: 1) it makes them know what and when to speak in a certain context 2) it has good audio with good pronunciation, making it easier to understand in improving listening skills 3) it helps them in learning new vocabulary because there are some new words that are not in everyday life. Keywords: Perception, English Learning, Learning Activities